Successful phytoremediation of crude-oil contaminated soil at an oil exploration and production company by plants-bacterial synergism. Issue 7 (7th June 2018) - Fatima, Kaneez; Imran, Asma; Amin, Imran; Khan, Qaiser M.; Afzal, Muhammad
ABSTRACT: Phytoremediation is a promising approach for the cleanup of soil contaminated with petroleum hydrocarbons. This study aimed to develop plant-bacterial synergism for the successful remediation of crude oil-contaminated soil. A consortia of three endophytic bacteria was augmented to two grasses, Leptochloa fusca and Brachiaria mutica, grown in oil-contaminated soil (46.8 g oil kg −1 soil) in the vicinity of an oil exploration and production company. Endophytes augmentation improved plant growth, crude oil degradation, and soil health. Maximum oil degradation (80%) was achieved with B. mutica plants augmented with the endophytes and it was significantly ( P < 0.05) higher than the use of plants or bacteria individually. Moreover, endophytes showed more persistence, the abundance and expression of alkB gene in the rhizosphere as well as in the endosphere of the tested plants than in unvegetated soil. A positive relationship ( r = 0.70) observed between gene expression and crude oil reduction indicates that catabolic gene expression is important for hydrocarbon mineralization. This investigation showed that the use of endophytes with appropriate plant is an effective strategy for the cleanup of oil-contaminated soil under field conditions.